The portfolio – a good educational practice (a review of publications) - Z. Zhelyazkova (Trakia Journal of Sciences)
The paper is a review article devoted to a brief overview of English-language publications on portfolio as a good tool for continuously improving the quality of education in secondary and higher-education schools. The study is an essential part of the activities of a research project aimed at creating an electronic institutional portfolio of the specialty Social Pedagogy – at the Faculty of Education, Trakia University - Stara Zagora; respectively, the method used is qualitative critical review. The intention of the project is practically justified by the need to present a university specialty to various users - present and potential students, alumni, employers and other business environments of social and educational services, partner institutions, including mentors of student placement practices, national and foreign and/or international corporative non-profit associations with a similar scope of educational activities sharing the same interest in the specialty for working in a net.